Inferior vena cava thrombosis as a complication of Crohn’s disease - G., Parthiban (International Journal of Advances in Medicine, 2018)
Twenty-nine years old male, a case of Crohn’s disease diagnosed by histopathology 5 years back, when he developed a perforative peritonitis. Resection and anastomosis was done, and he was started on Mesalamine therapy. Patient stopped the drug 8 months back and presented with cough for 1-month duration. HRCT chest showed IVC thrombosis. CECT abdomen showed intrahepatic extension of thrombus with active colitis and absent left testicle in scrotum with no intra-abdominal testicle. Coagulation parameters were normal. Colonoscopy and biopsy was done showing features of active Crohn’s disease. Patient was restarted on Mesalamine and anticoagulation. Follow up imaging showed features of resolution of thrombus.